ATTITUDES AND INTENTIONS OF CROSS-GENERATIONAL EMPLOYEES TOWARD THE UTILIZATION OF AI IN UNIVERSITIES - Muhammad Raka Fadhillah; Hari Supriyadi; Yuniasih Tinekaningrum (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates the attitudes and intentions of cross-generational employees toward the utilization of artificial intelligence (AI) in universities. Using data from 40 staff of research department as a respondents measured with a Likert scale, results show that attitudes toward AI were generally neutral, leaning positive (mean 3.33), while intentions to use AI were relatively high (mean 3.55). Despite attitudes not being fully positive, intentions remained strong, suggesting a readiness to adopt AI if organizational support is provided. No statistically significant differences were found between Generations X, Y, and Z in either attitudes or intentions, although minor variations existed. The findings indicate that AI adoption in universities has the potential for broad cross-generational support, particularly if accompanied by targeted training, education, and communication strategies. Tailored approaches for older generations can help reduce resistance, while Millennials and Gen Z can be empowered as agents of change. Cross-generational mentoring and equal access to AI-related learning opportunities are essential to foster a technology-inclusive workplace in higher education.